UPAYA EDUKASI PENCEGAHAN PENYAKIT DISLIPIDEMIA MELALUI INFORMASI BROSUR PADA LANSIA DI KELURAHAN PANAU, KOTA PALU - Ismail, Ihwan; Khildah Khaerati; Muhammad Fahrul Hardani; Andi Athira Masyta; Ririn Hardani; Yuliet (JURNAL PENGABDIAN FARMASI DAN SAINS, 2024)
Dyslipidemia is a medical condition caused by a lipid metabolism disorder in the body. In the early stages, dyslipidemia often shows no symptoms or complaints, so many sufferers are unaware of their condition. However, examinations of total cholesterol, low-density lipoprotein (LDL), and triglyceride levels often show elevated results in people with dyslipidemia. Public awareness of the dangers of dyslipidemia remains low, particularly among the elderly. To increase understanding and awareness of dyslipidemia, a community service activity was conducted in Pana Village. This activity began with cholesterol level checks. Following this, a presentation was given on the dangers of dyslipidemia, especially among the elderly, and the importance of maintaining a healthy lifestyle to prevent risks of heart disease, stroke, and even death. This counseling session focused on lifestyle changes that can help control cholesterol levels, such as regulating diet, exercising regularly, and avoiding unhealthy habits like smoking. Out of 95 participants who underwent cholesterol testing, the results showed that 46 elderly individuals (43%) had cholesterol levels below 200 mg/dl, which is still considered within normal limits. However, 54 elderly individuals (57.3%) had cholesterol levels above 200 mg/dl, indicating a high prevalence of dyslipidemia in this age group. These findings emphasize the importance of health education for the elderly, so they become more aware of the risks of dyslipidemia and are motivated to adopt a healthier lifestyle to prevent serious complications.